Calculation of multicomponent vapor–liquid critical point using the Dividing Rectangles global optimization algorithm. (3rd May 2017) - Rabieh, Milad M.; Nasernejad, Bahram; Dadvar, Mitra; Modarres, Hamid
ABSTRACT: In this paper, the Dividing Rectangles (D.R.) global optimization technique is used to predict the critical temperature and pressure for multicomponent systems. The D.R. optimization algorithm is a fast and reliable optimization method without any need for adjustable parameters, initial guesses or objective function derivation. For calculating the critical point the tangent plane distance (TPD) in terms of the Helmholtz energy is selected. The Peng Robinson (PR) equation of state is applied for determining thermodynamic relations. The procedure of the critical point calculation by means of global optimization is described stepwise in order to clarify the concept and method of programing. The D.R.-based computer program is tested for some multicomponent systems and the results are compared with the Simulated Annealing (SA) global optimization method and with experimental data. The results indicated that the number of the objective function calls (the main parameter that increases the speed and efficiency of an optimization algorithm) is reduced to one twentieth with almost the same accuracy.